2020
DOI: 10.1177/1049909120960441
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extrapyramidal Symptoms in Cancer Patients Referred to Palliative Care: A Multicenter Observational Study (JORTC PAL12)

Abstract: Background: Neuroleptics are commonly used in palliative care settings. However, adverse events of neuroleptics, known as extrapyramidal symptoms (EPSs), might be overlooked in clinical practice. We conducted this study to explore the prevalence of EPSs in palliative care setting. Methods: This multicenter, prospective, observational study included patients who 1) were referred to either a specialist palliative care team or a palliative care unit, 2) had a diagnosis of cancer, and 3) were ≥20 years of age. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…EPS includes disturbances in movement, tone, and/or posture, dystonia, parkinsonian signs, tardive dyskinesia, and tardive akathisia [ 16 , 17 ]. EPS occurs due to disturbances in the dopaminergic neurons in the central nervous system [ 18 ]. It also commonly occurs with medication use, especially with the use of antipsychotic medications such as haloperidol, risperidone, olanzapine, chlorpromazine, and prochlorperazine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EPS includes disturbances in movement, tone, and/or posture, dystonia, parkinsonian signs, tardive dyskinesia, and tardive akathisia [ 16 , 17 ]. EPS occurs due to disturbances in the dopaminergic neurons in the central nervous system [ 18 ]. It also commonly occurs with medication use, especially with the use of antipsychotic medications such as haloperidol, risperidone, olanzapine, chlorpromazine, and prochlorperazine.…”
Section: Discussionmentioning
confidence: 99%
“…EPS has been reported in up to 60% of patients taking long-term antipsychotics [ 19 ]. Ishiki et al investigated the prevalence of EPS in cancer patients undergoing palliative therapy [ 18 ]. They found that 14.8% of patients with EPS had metastasis to the brain, although some of them may have taken medications that caused the EPS [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation